Morphogen-driven differentiation is precluded by physical confinement in human iPSCs spheroids - Alsehli, Haneen S.; Roy, Errin; Williams, Thomas; Kuziola, Alicja; Guo, Yunzhe; Dreiss, Cecile A.; Green, Jeremy B.A.; Gentleman, Eileen; Danovi, Davide (Frontiers in Bioengineering and Biotechnology, 2024)
Cell lineage specification is tightly associated with profound morphological changes in the developing human embryo, particularly during gastrulation. The interplay between mechanical forces and biochemical signals is poorly understood. Here, we dissect the effects of biochemical cues and physical confinement on a 3D in vitro model based on spheroids formed from human induced pluripotent stem cells (hiPSCs). First, we compare self-renewing versus differentiating media conditions in free-floating cultures and observe the emergence of tri-germ layers. In these unconfined conditions, BMP4 exposure induces polarised expression of SOX17 in conjunction with spheroid elongation. We then physically confine spheroids using PEGpeptide hydrogels and observe dramatically reduced SOX17 expression, albeit rescued if gels that soften over time are used instead. Our study combines high-content imaging, synthetic hydrogels, and hiPSCs-derived models of early development to define the drivers that cause changes in the shape and the emergence of germ layers.